A new approach to the granulation of beta-cyclodextrin inclusion complexes - Castro, Ana Doris de [UNESP]; Silva, Nelson P. [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Evangelista, Raul Cesar [UNESP]; Freitas, Luis A. P.; Gremião, Maria Palmira Daflon [UNESP] (Elsevier B.V. Sa, 2010)
Cyclodextrins (CDs) are annular oligosaccharides containing 6-12 glucose unities joined together by alpha-1,4 bonds. They have a conical-truncated shape with a lipophilic cavity in which different molecules can be included resulting in a stable inclusion complex. The cyclodextrins have been widely applied in pharmaceutical technology with the objective of increasing the solubility, stability and bioavailability of drugs in different pharmaceutical dosage forms, such as tablets. In order to obtain beta-CD tablets, liquid dispersions of drug/beta-CD are usually submitted to different drying processes, like spray-drying, freeze-drying or slow evaporation, being this dry material added to a number of excipients. However, such drying processes can generate particulate materials showing problems of flow and compressibility, needing their conversion into granulates by means of wetting with granulation liquid followed by additional drying. In this work, the main objective was to evaluate the preparation of tablets without the need of this additional drying step. For this purpose an aqueous dispersion containing acetaminophen/beta-CD complex and cornstarch was dried using a spouted bed and the obtained granules were compressed in tablets. Acetaminophen was used as model drug due to its low water solubility and the inexpensive and widely available cornstarch was chosen as excipient. Acetaminophen powder was added into a beta-cyclodextrin solution prepared in distilled water at 70 degrees C. Stirring was kept until this dispersion cooled to room temperature. Then cornstarch was added and the resulting dispersion was dried in spouted bed equipment. This material was compressed into tablets using an Erweka Korsh EKO tablet machine. This innovative approach allowed the tablets preparation process to be carried out with fewer steps and represents a technological reliable strategy to produce beta-cyclodextrin inclusion complexes tablets. (C) 2010 Elsevier By. All rights reserved.
Keywords: beta-Cyclodextrin; Spouted bed; Granulation; Tablets; Granules